Life imprisonment in India: will the prison doors ever open for life-sentenced prisoners? - Bedi, Shruti (Life Imprisonment in Asia, 2023)
Imprisonment for life is an authorised form of punishment under the Indian Penal Code, 1860 (IPC) and other cognate laws in India. Much debate and discussion about life imprisonment have been undertaken by Parliament, the Law Commission of India, state legislatures and the Indian judiciary. This chapter seeks to throw light on the current legal position of this form of punishment concerning its character and mode of execution in India. The chapter also delves into the imposition of ‘whole life sentences’, which have been legitimised in India since 2015. Such is the popularity of these sentences that they are increasingly being imposed. In this context, the chapter shares pertinent data and analyses trends on the imposition of life sentences, in particular whole life sentences. It calls for the imminent need to revisit whole life sentences and other existing anomalies in the sentencing procedure, in the light of grave human rights concerns that besiege such sentences.